Pengaruh Model Pembelajaran Kooperatif Tipe Snowball Throwing terhadap Hasil Belajar Siswa Mata Pelajaran IPA Kelas V di Madrasah Ibtidaiyah Al-Mursyid Citeureup Bogor - Mursid, Kiki Barkah; Suryana, Agus; Sugiyanto, Agus (Ikatan Dai Indonesia, 2022)
The learning activities carried out by the teachers at MI Al-Mursyid have been impressed that only active teachers. The teacher mostly uses the discussion method when learning takes place, but the discussion is still ineffective so that students tend to be passive in accepting the subject matter provided by the teacher. This results in student activity and learning outcomes to be very low. With this background, researchers are interested in examining whether there is an effect of the Snowball Throwing Cooperative Learning Model on Student Learning Outcomes. The research was conducted at MI Al-Mursyid, Citeureup District, Bogor Regency. The study population was 153 students while the sample was 20 people. Researchers used an experimental class, namely class V with a total of 20 students. The instrument used was a test to measure student learning outcomes in the form of a multiple choice test of 20 questions. The data analysis technique used is descriptive statistical analysis and inferential statistical analysis with t-test. Based on the results of the descriptive analysis, the average value obtained before applying the Snowball Throwing model was 57.60 for pretest and 81.55 for posttest. Based on the results of inferential statistical analysis t count 11.31 and t table 2.10. Because tcount> ttable (11.31> 2.10), then H0 is rejected and Ha is accepted. So, it can be concluded that the accepted hypothesis is that the Snowball Throwing learning model in science learning has a significant effect on the learning outcomes of grade V students at MI Al-Mursyid.